Juvenile Rheumatoid Arthritis (JRA) - Elymbra, Dahnul; Ramayati, Rafita; Rusdidjas, Rusdidjas (Indonesian Pediatric Society, 1990)
A case of Juvenile Rheumatoid Arthritis in a 12-year-old girl is reported; the patient had been suffering since she was 2.5 years old. The diagnosis was made based on history, clinical symptoms, radiology and laboratory findings. The patient showed abnormalities of the eyes, namely left papilla, atrophy and right papillar edema. Osteoporosis was found in the proximal area of the right and left ulna and radius as well as in the lateral epicondylus. Laboratory findings such as rheumatoid factor, LE cells and ANA were negative; the C, was low; AST0 was within normal ranges and the serum creatinine was 2.3 mg%. When this paper was made the patient was still under outpatient treatment; complaints of arthralgia disappeared after she had been treated with aspirin.